Corps (é)conduits : La construction d’un regard-machine dans Crash (1996) et Cosmopolis (2012) de David Cronenberg - Guilhem Billaudel (Sillages Critiques)
“It is necessary to identify two point of views [in Crash]: that of the characters […] and that of the audience”, Paul-Marie Battestini writes in his work on David Cronenberg’s film. It may nevertheless be fruitful to question the possibility of a third perspective, that of the cars on which Crash and Cosmopolis focus, inasmuch as they are essential and close to being actual characters. This article attempts to observe the changing status of vehicles within the carnal, economic and affective relations displayed in the two films. Crash et Cosmopolis shall not, however, be apprehended as exceptions, neither in relation to North-American film history nor to Cronenberg’s work itself. Attachment, dependency and eroticism as represented here are but the outcome of the way film history has given an increasingly complex and central focus to the car, paralleling its ever-growing fetishization within Western culture. When narrating the quest for the perfect car-crash in a group of fin de siècle fetishists or the physical and mental dissolution of a trader locked in his limousine, Cronenberg always makes the car become more than a prop or a means of transportation. A death machine, a magnifying glass, a coffin-to-be or a metaphorical cradle, it is the true protagonist of works focusing on desire and its variations. Beyond the pleasure/pain and protection/destruction binaries, it is therefore essential to question the way Cronenberg explores the possibility of a focal shift, from the “new flesh” to a machine-centered perspective.